EYE-HEALTH CAN START ON THE LIPS - Cristina Dancă; Gabriela Dimitriu; Andrei Ionuț Cucu; Camelia Margareta Bogdănici; Dana Mihaela Turliuc; Mihaela Roxana Popescu; Claudia Florida Costea (Romanian Society of Oral Rehabilitation, 2019)
Primary open-angle glaucoma (POAG) is a progressive optic nerve disease characterized by neurodegeneration of retinal ganglionic cells and their axons. Local inflammatory responses are implicated in the pathology of glaucoma. Despite the large number of studies conducted to identify non-genetic risk factors, only race, age, intraocular pressure, and corneal thickness were consistently identified. Of these, only intraocular pressure is a modifiable factor and also the only means we have at our fingertips to influence the development of glaucomatous disease. Tooth loss or periodontal disease is associated with systemic endothelial dysfunction, which has been implicated in primary open-angle glaucoma. The main hypothesis behind this correlation is that infectious and inflammatory processes located in the teeth can produce factors that will be released into systemic blood circulation. At the eye level, these factors are responsible for triggering the inflammatory response, neurodegeneration and, in some cases, open-angle glaucoma. Mounting evidence suggests that neuroinflammation is a key process in glaucoma, while the precise roles are yet to be discovered. In this article we reviewed the literature on neuroinflammation in glaucoma triggered by oral cavity microbiota and infiltration of peripheral immune cells. In conclusion, if an association between dental health, the oral microbiome and POAG were established, this would have potentially significant implications for the understanding and management of glaucoma and possibly other neurodegenerative diseases and we will be able to work together in order to prevent both glaucoma and dental diseases.